Child–Parent Interventions for Childhood Anxiety Disorders: A Systematic Review and Meta-Analysis. (May 2014) - Brendel, Kristen Esposito; Maynard, Brandy R.
Objective: This study compared the effects of direct child–parent interventions to the effects of child-focused interventions on anxiety outcomes for children with anxiety disorders. Method: Systematic review methods and meta-analytic techniques were employed. Eight randomized controlled trials examining effects of family cognitive behavior therapy compared to individual or group child-only therapy met criteria. Results: The overall mean effect of parent–child interventions was 0.26, 95% confidence interval [0.05, 0.47], p < .05, a small but positive and significant effect, favoring child–parent interventions. Results of the heterogeneity analysis were not significant ( Q = 8.08, df = 7, p > .05, I 2 = 13.41). Discussion: Parent–child interventions appear to be more effective than child-focused individual and group cognitive behavioral therapy in treating childhood anxiety disorders. Implications for practice and research are discussed.